2014
DOI: 10.3171/2014.6.focus14127
|View full text |Cite
|
Sign up to set email alerts
|

Medical and surgical management of spinal epidural abscess: a systematic review

Abstract: Object Spinal epidural abscess (SEA) is a rare condition that has previously been treated with urgent surgical decompression and antibiotics. Recent availability of MRI makes early diagnosis possible and allows for the nonoperative treatment of SEA in select patients. The first retrospective review of medically and surgically managed SEA was published in 1999, and since that time several other retrospective institutional reports have been published. This study review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
172
2
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(198 citation statements)
references
References 22 publications
(75 reference statements)
13
172
2
11
Order By: Relevance
“…However, a recent systematic review has shown an increasing number of patients being managed nonoperatively when presenting with back pain in the absence of neurology, compared to previously published literature, with no statistically significant difference in outcomes between those in the different treatment groups. 22 Primary nonoperative treatment with antibiotics has been described in the literature. 3,22 Several factors to favour medical management have been identified, including patients over 50 years old or with significant co-morbidities; the absence of neurology, or conversely, neurological dysfunction that has been persistent for more than 36 hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent systematic review has shown an increasing number of patients being managed nonoperatively when presenting with back pain in the absence of neurology, compared to previously published literature, with no statistically significant difference in outcomes between those in the different treatment groups. 22 Primary nonoperative treatment with antibiotics has been described in the literature. 3,22 Several factors to favour medical management have been identified, including patients over 50 years old or with significant co-morbidities; the absence of neurology, or conversely, neurological dysfunction that has been persistent for more than 36 hours.…”
Section: Discussionmentioning
confidence: 99%
“…22 Primary nonoperative treatment with antibiotics has been described in the literature. 3,22 Several factors to favour medical management have been identified, including patients over 50 years old or with significant co-morbidities; the absence of neurology, or conversely, neurological dysfunction that has been persistent for more than 36 hours. As in our case, extensive multi-regional SEA has also been described as an indication for conservative management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…İnsidansı 2 ile 12,5/10000 arasında değişiklik göstermekle birlikte vertebral enfeksiyonların yaklaşık olarak 1/14'ini oluşturur (1,8,10) .…”
unclassified
“…SEA'lara en sık neden olan etkenler sırasıyla; Stafilokokus aureus (metisiline dirençli veya duyarlı suşlar) (%50-90), streptokoklar (%8-17) ve Gram negatif bakteriler (%7-13) iken, (%10-17) arasında etken tespit edilememektedir (1,2,18) . SEA'ler sıklıkla lomber (%30-48) ve torakal (%30-42) bölgede görülmekteyken, daha az sık-lıkla servikal (%24-26) bölgede görülmektedir (1,17) .…”
unclassified